2020
DOI: 10.3389/fnmol.2020.577622
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Peptide Impact on Synaptic Function and Neuroepigenetic Gene Control Reveal New Therapeutic Strategies for Alzheimer’s Disease

Abstract: Amyloid-β (Aβ) peptides can form protease-resistant aggregates within and outside of neurons. Accumulation of these aggregates is a hallmark of Alzheimer’s disease (AD) neuropathology and contributes to devastating cognitive deficits associated with this disorder. The primary etiological factor for Aβ aggregation is either an increase in Aβ production or a decrease in its clearance. Aβ is produced by the sequential activity of β- and γ-secretase on the amyloid precursor protein (APP) and the clearance is media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…These findings emphasize the need to understand the physiological and pathological roles of Aβ in order to improve current amyloid based therapeutic strategies (Karisetty et al, 2020). As AD is a multifactorial disease, targeting AD related processes such as tau pathology, synaptic activity, neural epigenetic regulation of AD associated genes, and inflammatory responses may provide alternative treatment strategies (Karisetty et al, 2020). In line with previous studies (De Vos et al, 2015;Hellwig et al, 2015;Portelius et al, 2015;Janelidze et al, 2016;Mattsson et al, 2016;Sanfilippo et al, 2016;Wang, 2019;Xue et al, 2020), we have found that elevated levels of CSF Ng were correlated with T-tau and P-tau in every diagnostic FIGURE 4 | Baseline CSF measures of Ng as predictors of conversion from CN to MCI or AD and MCI to AD.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…These findings emphasize the need to understand the physiological and pathological roles of Aβ in order to improve current amyloid based therapeutic strategies (Karisetty et al, 2020). As AD is a multifactorial disease, targeting AD related processes such as tau pathology, synaptic activity, neural epigenetic regulation of AD associated genes, and inflammatory responses may provide alternative treatment strategies (Karisetty et al, 2020). In line with previous studies (De Vos et al, 2015;Hellwig et al, 2015;Portelius et al, 2015;Janelidze et al, 2016;Mattsson et al, 2016;Sanfilippo et al, 2016;Wang, 2019;Xue et al, 2020), we have found that elevated levels of CSF Ng were correlated with T-tau and P-tau in every diagnostic FIGURE 4 | Baseline CSF measures of Ng as predictors of conversion from CN to MCI or AD and MCI to AD.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, some studies have demonstrated the role of Aβ in neuroprotection, synaptic function and memory consolidation ( Lazarevic et al, 2017 ; Finnie and Nader, 2020 ). These beneficial effects are Aβ level and species specificity ( Karisetty et al, 2020 ). Picomolar levels and monomers proved to be beneficial, while high levels and soluble oligomers proved to be harmful ( Karisetty et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cleaved product of the glycoprotein amyloid precursor protein is AB, which aggregates into AB plaques. According to the amyloid cascade hypothesis, it is these plaques that are responsible for AD pathology 37 . Soluble Ab species can bind to and produce toxicity to various neuronal receptors, leading to cellular oxidative stress and epigenetic-mediated transcription disorders 38 .…”
Section: Discussionmentioning
confidence: 99%